2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5332828
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous non-invasive brain-actuated control of an intelligent wheelchair

Abstract: Abstract-In this paper we present further results of our asynchronous and non-invasive BMI for the continuous control of an intelligent wheelchair. Three subjects participated in two experiments where they steered the wheelchair spontaneously, without any external cue. To do so the users learn to voluntary modulate EEG oscillatory rhythms by executing three mental tasks (i.e., mental imagery) that are associated to different steering commands. Importantly, we implement shared control techniques between the BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 10 publications
0
78
0
1
Order By: Relevance
“…In this paper we have described one of the first implementations of a shared-control BCI telepresence robot that is related to our previous work with wheelchairs [11], [12], [13], [14]. In the current paper, however, shared control only deals with lowlevel obstacle avoidance and it relies on very simple infrared sensors (as opposed to expensive laser range finders on the wheelchairs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we have described one of the first implementations of a shared-control BCI telepresence robot that is related to our previous work with wheelchairs [11], [12], [13], [14]. In the current paper, however, shared control only deals with lowlevel obstacle avoidance and it relies on very simple infrared sensors (as opposed to expensive laser range finders on the wheelchairs).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, for them, a semi-autonomous approach is more suitable for a BCIcontrolled telepresence robot, where the intelligent system helps the human user to cope with problematic situations such as obstacle detection and avoidance [9]. Such a semiautonomous framework has been largely explored for assistive wheelchairs [4], [10], including brain-controlled wheelchairs [11], [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, so far control tasks based on human EEG have been limited to simple exercises such as moving a computer cursor or opening a hand orthosis [7]- [8]. However, recently we have shown that an EEG-based BCI can also make possible the continuous control of a mobile robot (emulating a motorized wheelchair) generating non-trivial trajectories among different rooms in a house-like environment [3]. The key idea here is that the user's mental states are associated with highlevel commands (e.g., "turn right at the next occasion") and that the robot executes these commands autonomously using the readings of its on-board sensors.…”
Section: Bci For Communication and Controlmentioning
confidence: 99%
“…In this paper we use a simple statistical classifier to illustrate the benefits of on-line learning with three beginner subjects. After a few sessions, two of these subjects reached a performance that, according to our previous experience, is close to allow them to start operating a brain-actuated device [1]- [3], and this despite the subjects have been trained without feedback (see Section 3). To the best of our knowledge, the issue of on-line learning in BCI has not been explored previously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation